La posta in gioco dell'uguaglianza tra Marx e Rousseau - Basso, Luca (Bollettino Filosofico, 2025)
The theme of the relationship between Marx and Rousseau, which has enjoyed some success in the past (in Italy, particularly with Galvano della Volpe’s book, Rousseau and Marx) and which has been largely overlooked in recent decades, is not only significant for the history of philosophy, but also has a number of important implications in terms of political theory. My article is divided into two parts. The first is devoted to Marx’s critical reading of Rousseau’s reflection, which would tend towards (only) political and not social emancipation. The second part focuses on the overall theoretical meaning of a comparison between Marx and Rousseau in relation to equality, beyond Marx’s explicit positions on Rousseau. The challenge is to articulate equality not in terms of levelling, but on the basis of a close connection with practices of social and political transformation. Keywords: Emancipation, Equality, Politics, Property, Society